Methodological proposal to enhance coexistence processes, in fifth grade students of headquarters No. 2 in the educational institution Manuel j del Ciénaga Magdalena Castillo (Docentes 2.0 Journal, 2019)
The purpose of this article was to unveil the theoretical foundations to enhance the processes of coexistence in students in fifth grade of primary school. Therefore, the postulates that theoretically based the study are oriented in Jares (2006); Torrego and Moreno, (2003); Melendro, (1997); Fernández, (2004) in addition to Megía, (2014); Backman (2014). In turn, its methodological route was supported by a qualitative approach applying a participatory action research design, taking as a sample student between 9 and 12 years of age. However, the results showed that the majority of children have few behaviors suitable for integration with social groups, it is also evident that some have disruptive families reflecting in them antivalores such as disrespect, irresponsibility, they also expressed Don't care about the consequences generated. Finally, it is concluded that the development of teaching strategies allows students to activate the sense of relevance, responsibility, commitment and respect for the same and for the other, therefore, the participation and integration of students in the realization through cooperative and collaborative work, showing respect for ideas as well as the consensus of the results.
Keywords: Processes; school life; education